Galaxy evolution in the post-merger regime. II -- Post-merger quenching peaks within 500 Myr of coalescence - Sara Ellison; Leonardo Ferreira; Vivienne Wild; Scott Wilkinson; Kate Rowlands; David R. Patton (The Open Journal of Astrophysics)
Mechanisms for quenching star formation in galaxies remain hotly debated, with galaxy mergers an oft-proposed pathway. In Ellison et al. (2022) we tested this scenario by quantifying the fraction of recently and rapidly quenched post-starbursts (PSBs) in a sample of post-merger galaxies identified in the Ultraviolet Near Infrared Optical Northern Survey (UNIONS). Compared with a control sample of non-interacting galaxies, Ellison et al. (2022) found PSBs to be a factor of 30-60 more common in the post-mergers, demonstrating that mergers can lead to quenching. However, the exact timing of this post-merger quenching was unconstrained. Thanks to our recent development of the Multi-Model Merger Identifier (MUMMI) neural network ensemble (Ferreira et al. 2024a,b), we are now able to predict the time since coalescence ($T_{PM}$) for the UNIONS post-merger galaxies up to $T_{PM} = 1.8$ Gyr, allowing us to further dissect the merger sequence and measure more precisely when quenching occurs. Based on a sample of 5927 $z<0.3$ post-mergers identified in UNIONS, we find that the post-coalescence population evolves from one dominated by star-forming (and starbursting) galaxies at $0 < T_{PM} < 0.16$ Gyr, through to a population that is dominated by quenched galaxies by $T_{PM} \sim 1.5$ Gyr. By combining the post-mergers with a sample of 15,831 spectroscopic galaxy pairs with projected separations $r_p<100$ kpc we are able to trace the evolution of quenching during the full merger sequence. We find a PSB excess throughout the post-merger regime, but with a clear peak at $0.16 < T_{PM} < 0.48$ Gyr. In this post-merger time range PSBs are more common than in control galaxies by factors of 30-100 (depending on PSB selection method), an excess that drops sharply at longer times since merger. We also quantify the fraction of PSBs that are mergers and find that the majority (75 per cent) of classically selected E+A are identified as either pairs or post-mergers, with a lower merger fraction (60 per cent) amongst PCA selected PSBs. The merger fraction of PSB galaxies also correlates strongly with stellar mass. Taken together, our results demonstrate that 1) galaxy-galaxy interactions can lead to rapid post-merger quenching within 0.5 Gyr of coalescence, 2) the majority of (but not all) PSBs at low $z$ are linked to mergers and 3) quenching pathways are diverse, with different PSB selection techniques likely identifying galaxies quenched by different physical processes with an additional dependence on stellar mass.